An evidence‐based approach to assessing surgical versus clinical diagnosis of symptomatic endometriosis. Issue 2 (28th May 2018) - Taylor, Hugh S.; Adamson, G. David; Diamond, Michael P.; Goldstein, Steven R.; Horne, Andrew W.; Missmer, Stacey A.; Snabes, Michael C.; Surrey, Eric; Taylor, Robert N.
Abstract: Challenges intrinsic to the accurate diagnosis of endometriosis contribute to an extended delay between the onset of symptoms and clinical confirmation. Intraoperative visualization, preferably with histologic verification, is considered by many professional organizations to be the gold standard by which endometriosis is diagnosed. Clinical diagnosis of symptomatic endometriosis via patient history, physical examination, and noninvasive tests, though more easily executed, is generally viewed as less accurate than surgical diagnosis. Technological advances and increased understanding of the pathophysiology of endometriosis warrant continuing reevaluation of the standard method for diagnosing symptomatic disease. A review of the published literature was therefore performed with the goal of comparing the accuracy of clinical diagnostic measures with that of surgical diagnosis. The current body of evidence suggests that clinical diagnosis of symptomatic endometriosis is more reliable than previously recognized and that surgical diagnosis has limitations that could be underappreciated. Regardless of the methodology used, women with suspected symptomatic endometriosis would be well served by a diagnostic paradigm that is reliable, conveys minimal risk of under‐ or over‐diagnosis, lessens the time from symptom development to diagnosis, and guides the appropriate use of medical and surgical management strategies. Abstract : Current research suggests that clinical diagnosis of symptomatic endometriosis is more reliable than generally considered and could offer an accessible alternative to surgical diagnosis.